On some novel optical solitons to the cubic-quintic nonlinear Helmholtz model - Khater, Mostafa M. A.; İnç, Mustafa; Tariq, Kalim U.; Tchier, Fairouz; Ilyas, Hamza; Baleanu, Dumitru (Springer, 2022)
The purpose of this study is to employ the Sine-Cosine expansion approach to produce some new sort of soliton solutions for the cubic-quintic nonlinear Helmholtz problem. The nonlinear complex model compensates for backward scattering effects that are overlooked in the more popular nonlinear Schrodinger equation. As a result, a number of novel traveling wave structures have been discovered. We also investigate the stability of solitary wave solutions for the governing model. Furthermore, the modulation instability is discussed by employing the standard linear-stability analysis. The 3D, contour and 2D graphs are visualized for several fascinating exact solutions to comprehend their behaviour.
Keywords: Analytical solutions; Helmholtz model; Optical soliton